Reformulasi Sentra Penegakan Hukum Terpadu menjadi Lembaga Independen Pemberantasan Tindak Pidana Pemilu - Madjid, Mario Agritama S W (Jurnal Penelitian Hukum De Jure, 2024)
The practice of implementing elections in Indonesia from time to time becomes an antinomy of the principle of honesty and fairness. This practice is evidenced by the increasing number of election violations, especially election crimes. This shows that the role of the Sentra Gakkumdu, which specifically functions to eradicate election crimes, has not been effective. The most highlighted issue regarding the existence of the Sentra Gakkumdu is the weak coordination and its limited nature as a forum between Bawaslu, the Police, and the Prosecutor’s Office. This research aims to describe the problematics of election criminal law enforcement in Indonesia and the reformulation of Sentra Gakkumdu into an Independent Institution for Eradicating Election Crimes. This research was conducted using normative juridical research. The results of this study show: First, the ineffectiveness of election criminal enforcement is caused by the limited time for handling cases, the weak institutional building of Gakkumdu which includes institutional nature, authority, human resource capacity and coordination between institutions in it. Second, it is necessary to reformulate the Gakkumdu Center into an Independent Institution for the Eradication of Election Crimes. The idea of making Gakkumdu an Independent Institution departs from several weaknesses in the existing institutional building plus the complexity of handling election crimes and speedy trial design requires a special institution that focuses on handling the eradication of election crimes. The institution will later take the form of an independent institution with prevention and prosecution functions, while. The institutional structure will consist of investigators, investigators, and permanent public prosecutors led by commissioners.